Caveat Emptor Doctrine: An Evaluation of Contract Act 1950 and Islamic Law: (Doktrin Caveat Emptor: Penilaian terhadap Akta Kontrak 1950 dan perundangan Islam) (Kanun: Jurnal Undang-undang Malaysia, 2021)
The caveat emptor practice, which is a doctrine introduced by common law since the 13th century, imposes the responsibility on purchasers to be fastidious during a transaction process. In this practice, sellers are not bound to reveal complete information they know to purchasers. In Malaysia, this doctrine is unclear in any legal provision. Therefore, this study aims to analyse the use of the doctrine of caveat emptor in the Contract Act 1950. Furthermore, this study also examines the perspective of Islamic law on the practice of this doctrine. This qualitative study uses document analysis approach to analyse the data collected. The findings revealed several provisions in the Contract Act 1950 that practice the doctrine of caveat emptor, despite the ambiguity of the provision in the Act. Meanwhile, according to Islamic law, the practice of the doctrine is deemed unsuitable as it is against the principles of Islamic law. Hence, this study recommends an amendment of the provision related to the caveat emptor practice in the Contract Act 1950.Keywords: Caveat emptor, contract, transaction, Contract Act 1950, terms and conditions